The socio-religio and political roles of the Rushdiah Club in Colonial Riau - Oktasari, Wiwin; Zakariya, Hafiz (2012)

(untitled)
The history of the Malay society in Riau shows that Riau played a leading role as the vanguard of tradition and culture in Indonesia through the development of writing. Riau produced many prominent writers in various fields: religion, art, medicine, literature, language, law and history. In light of Riau prominence in culture and writing in the Malay Archipelago, this study examines the printing and publishing practices in Riau-Lingga Sultanate during the period of Dutch colonialism. Specifically, it analyzes the development of print culture in the last decades of 19th and early 20th centuries and its impact on the Malay society and as a reaction to the Dutch colonialism. It would analyse these issues through a case study of a literati-publisher of Riau-Lingga, Rushdiah Club and its impacts on politics, religion, and culture. Politically, this study will examine how printing activities were used as a non-violent form of resistance to Dutch colonialism in Riau-Lingga at the time when Riau people’s call for freedom was constantly and violently suppressed by the colonial regime. From the religious perspective, it will also examine how Rusydiah Club utilized printing for the construction of Islamic thought and culture.